Multikulturalisme dan Pewarisan Nilai Sosial-Keagamaan: Studi Etnopedagogi Masyarakat Sunda Wiwitan di Cimahi - Silaban, Robintang Jegesari; Al Fahrezi, Ahmad Fathan; Sulaeman, Amanda Saputri; Fadilah, Siti Nurul; Christy, Joana; Gultom, Tresia Cilita; Wilodati, Wilodati; Supriyono, Supriyono (Universitas Cokroaminoto Yogyakarta, 2026)
The Sunda Wiwitan community in Cimahi faces the challenge of preserving cultural values ​​and identity in a multicultural urban environment. This research uses a qualitative case study approach to examine the mechanisms of value transmission and the influence of multiculturalism on socio-religious life. The results show that values ​​are inherited through families and traditional communities, while multiculturalism encourages adaptation without eliminating core teachings. Furthermore, urban life strengthens tolerance and inclusive religious practices.